Lexical Selection in Multi-Word Production - Janssen, Niels; Caramazza, Alfonso (Frontiers in Psychology, 2011)
In multi-word utterances, target words need to be selected in the context of other target words. In the present study, three hypotheses were tested that differed in their assumptions about whether the lexical selection mechanism considers the activation levels of the other target lexical representations, and whether it takes into account their grammatical class properties. Participants produced adjective+noun and noun+noun utterances in response to colored word and picture+word stimulus displays. In both types of utterances, the frequency of the first and second response was manipulated. The results revealed an effect of the frequency of the second response that did not depend on the utterance type, and additive effects for the frequency of the first and the second response in both utterance types. These results are interpreted in terms of a model of lexical selection that assumes that selection is non-competitive.